Quantifying ETo Maps Across Egypt: A Remote Sensing Approach to Address Water Needs for Agricultural Irrigation - Hesham Ezz; Mohamed Abdelwares (Engineering Research: Perspectives on Recent Advances Vol. 4, 2025)
Egypt faces acute water scarcity, posing a critical challenge to its agricultural sector, which consumes approximately 85% of the nation’s water resources. This challenge is compounded by the government’s horizontal agricultural expansion strategy to meet the demands of rapid population growth. To support sustainable water resource management, this study integrates GIS with the FAO Penman-Monteith equation to calculate reference evapotranspiration (ETo) across Egypt using high-resolution climate data (1970–2000) from over 10,000 spatial points. By leveraging remote sensing and advanced spatial interpolation techniques, the study generates monthly ETo maps, providing precise insights into the spatial and temporal variability of ETo. The results reveal significant seasonal trends: the highest mean ETo value (9.5 mm/day) occurs in June, while the lowest (3.28 mm/day) is observed in December. A clear north-to-south gradient in ETo values is identified, influenced by temperature and solar radiation, with the Red Sea Coast exhibiting lower ETo due to higher humidity levels. These findings hold practical implications for sustainable agricultural planning and water conservation. Policymakers can use high-resolution ETo maps to optimize irrigation schedules, reduce water wastage, and identify low-evapotranspiration zones suitable for agricultural expansion. This scalable methodology, incorporating remote sensing for enhanced data collection, offers a robust framework for addressing water management challenges in Egypt and other arid regions globally.